Optimization of Ultrasonic-Assisted Extraction of Curcuminoids from Temulawak (Curcuma xanthorrhiza Roxb.) Using Response Surface Methodology - Yusnira; Kasman Ediputra (Jurnal Penelitian Pendidikan IPA, 2025)
Temulawak (Curcuma xanthorrhiza Roxb.) is a native Indonesian medicinal plant that has a lot of curcuminoids with strong pharmacological activity. However, traditional extraction procedures don't always work well or provide good quality extracts. The goal of this research is to find the best way to get curcuminoids out of temulawak utilizing ultrasonic-assisted extraction (UAE) and response surface methodology (RSM). The Box-Behnken Design was used to optimize the process with three independent variables: ultrasonic power (200–400 W), extraction duration (20–60 minutes), and the ratio of material to solvent (1:15–1:35 g/mL). We used validated HPLC to look at curcuminoids, the DPPH technique to measure antioxidant activity, and a second-order polynomial model to look at the data. The mathematical model shows a good fit (R² = 0.9847), with all variables having a significant impact on the curcuminoid yield. The best results were achieved with an ultrasonic power of 354 W, an extraction time of 52 minutes, and a material to solvent ratio of 1:22 g/mL, leading to a total curcuminoid yield of 23.4±0.6 mg/g of simplicia and an antioxidant activity IC₅₀ of 31.2±1.1 μg/mL. The enhanced UAE process gave 8.4 times more yield than maceration and took 28 times less time to extract. The improved UAE is a quick and long-lasting way to get curcuminoids out of temulawak with a high yield and high-quality extract. This study gives scientists the information they need to create turmeric extraction technologies on an industrial scale to help Indonesia's pharmaceutical and nutraceutical businesses.